The impact of hormones on lung development and function: an overlooked aspect to consider from early childhood - Pelizzo, Gloria; Calcaterra, Valeria; Baldassarre, Paola; Marinaro, Michela; Taranto, Silvia; Ceresola, Michele; Capelo, Gerson; Gazzola, Cassandra; Zuccotti, Gianvincenzo (Frontiers in Endocrinology, 2024)
The impact of hormones on the respiratory system constitutes a multifaceted and intricate facet of human biology. We propose a comprehensive review of recent advancements in understanding the interactions between hormones and pulmonary development and function, focusing on pediatric populations. We explore how hormones can influence ventilation, perfusion, and pulmonary function, from regulating airway muscle tone to modulating the inflammatory response. Hormones play an important role in the growth and development of lung tissues, influencing them from early stages through infancy, childhood, adolescence, and into adulthood. Glucocorticoids, thyroid hormones, insulin, ghrelin, leptin, glucagon-like peptide 1 (GLP-1), retinoids, cholecalciferol sex steroids, hormones derived from adipose tissue, factors like insulin, granulocyte-macrophage colony-stimulating factor (GM-CSF) and glucagon are key players in modulating respiratory mechanics and inflammation. While ample evidence underscores the impact of hormones on lung development and function, along with sex-related differences in the prevalence of respiratory disorders, further research is needed to clarify their specific roles in these conditions. Further research into the mechanisms underlying hormonal effects is essential for the development of customizing therapeutic approaches for respiratory diseases. Understanding the impact of hormones on lung function could be valuable for developing personalized monitoring approaches in both medical and surgical pediatric settings, in order to improve outcomes and the quality of care for pediatric patients.